GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK EMPUNALA PERIODE MARET – MEI 2023 - Priyoherianto, Andri; Fitriany, Erna; Legowo, Deny Budi; Arif, M. Rizky (Jurnal Riset Kefarmasian Indonesia, 2024)
Pharmaceutical services are health services that have an important role in realizing health quality. Pharmaceutical services apart from being a 2 demand for professionalism such as a factor that attracts consumers' interest in purchasing drugs at pharmacies in order to obtain patient satisfaction. The purpose of this study was to describe the level of patient satisfaction with pharmaceutical services at the Empunala Drug store and to improve the quality of pharmaceutical services at the Empunala Drug store. This Research is descriptive non-experimental with incidental sampling, data collection using a questionnaire. The results of the study on the level of patient satisfaction with pharmaceutical services at the Empunala Drug store period March until May 2023 concluded on the Reliability dimension is 76%, the Responsiveness dimension is 78%, the Assurance dimension is 78%, the Emphaty dimension is 77%, and the Tangible dimension is 80%.